Assessment of daily dietary intake of Hg and some essential elements in diets of children from the Amazon region - Farias, Luciana Aparecida; Fávaro, Déborah Inês Teixeira; Maihara, Vera Akiko; Vasconcellos, Marina Beatriz Agostini; Yuyama, Lucia Kiyoko Ozaki; Aguiar, Jaime Paiva Lopes; Alencar, F. J. (Journal of Radioanalytical and Nuclear Chemistry, 2006)
Daily dietary intake of Hg and some essential elements in diets of children from communities in the Jaú National Park, Amazon region, were assessed. Diet samples were analyzed for total Hg content using cold vapor atomic absorption spectrometry and Ca, Fe, K, Na, Se and Zn contents by instrumental neutron activation analysis. The weekly tolerable provisional intake for Hg in the communities studied varied from 13 to 57 μg of Hg per kg of body weight, exceeding the limit of 5 μg·kg-1 set by the WHO. Comparison of the daily dietary intake values to the new Dietary Reference Intakes (4-8 years), showed prevalence of inadequacy. © 2006 Akadémiai Kiadó.
Keywords: Calcium; Iron; Mercury; Potassium; Selenium; Sodium; Zinc; Atomic Absorption Spectrometry; Child; Child Nutrition; Cold Vapor Atomic Absorption Spectrometry; Data Analysis; Dietary Intake; Dietary Reference Intake; Human; Instrumental Neutron Activation Analysis; Neutron Activation Analysis; Normal Human; Nutritional Deficiency; Practice Guideline; World Health Organization